A retrospective review of lung disease in adolescents living with human immunodeficiency syndrome - Naicker, Janani (Department of Medicine, 2025)
Chronic lung disease (CLD) is common in adolescents living with Human Immunodeficiency Virus (ALHIV), many of whom have survived early childhood respiratory infections and immune dysregulation. Little is known about the characteristics of ALHIV with CLD. Understanding the characteristics of this population is key to guiding service design, informing preventative strategies, and identifying tailored therapeutic interventions for preserving lung function and optimizing respiratory health. Methods: We retrospectively reviewed the clinical records of a historical cohort of adolescents aged 12 years to 20 years, diagnosed with vertically transmitted HIV and presenting with chronic lung disease to the Adolescent Respiratory Clinic of Groote Schuur Hospital between 1 January 2015, and 1 January 2023. Demographic data, details on HIV diagnosis, treatment history, lung function data, radiological data, clinical history and examination data, and microbiological data were analysed. Results: Seventeen patient records were reviewed. The median age at first visit was 16.9 years (interquartile range (IQR)15.2 to 18.7), and 58.9% (10/17) were female. The median age at HIV diagnosis was 1.1 years (IQR 1- 2), with a median duration of ART treatment of 13.2 years (IQR,8.6- 15.6), reflecting early HIV diagnosis and treatment initiation. The median CD4 nadir was 243 cells/mm3 (IQR 140- 516) and 16/17 patients had more than two prior episodes of pulmonary tuberculosis (PTB). Growth stunting was a common feature with a median BMI 17.7 kg/m2 (IQR 16.4- 19.8) and 16 /17 participants plotting below the 50th population centile of height-for-age. Radiological evidence of bilateral lung disease with bronchiectasis and cavitation was ubiquitous. Haemophilus influenzae was isolated in 12/17 (70.6%) patients and Methicillin-resistant staphylococcus aureus (MRSA) in 2/17 (11.7%) patients). The median FVC as a percentage of predicted values was 51.7% (IQR, 41.1- 60.8) and the median pre- bronchodilator FEV1/FVC ratio was 65%, (IQR of 57.8 to 74.3). indicating mixed spirometric defects. There was no significant bronchodilator response in any of the participants. Conclusion: Among ALHIV with CLD, there was a high prevalence of both airway and parenchymal lung disease, as well as severe growth impairment. Prior PTB was a common respiratory insult, despite early ART initiation. More needs to be done to prevent PTB, reduce the burden of recurrent respiratory infections, and to preserve long-term respiratory health in this vulnerable population. What the study adds: This study characterised a cohort of adolescents living with HIV and chronic lung disease in South Africa. Prior tuberculosis was common, and extensive bilateral structural lung abnormalities were universal. A significant proportion of the cohort exhibited severe growth impairment. Taken together, this study identifies ALHIV and CLD as a population with a high burden of respiratory deficits. Evidence-based secondary prevention and therapeutic strategies are needed to ensure the long-term preservation of lung function in these individuals.